The Dynamism and Transformation of “Tradition”: Factors Affecting the Development of Powwows in Southwestern Ontario - Hoefnagels, Anna (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2007)
AbstractIn this article the origins of selected powwows in southwestern Ontario are examined drawing on interviews with organizers and participants as well as media analysis. The author illustrates the complicated history of and influences on these gatherings, and she also highlights some of the ongoing challenges inherent in organizing these gatherings. The nuances of the term “tradition” vis-à-vis contemporary cultural gatherings that continue to change from year to year are also explored.